Technology-based Integrative Strategy in Improving Islamic Education Teachers Competence - Farhan Mahara; Hafidz Hafidz (Yayasan Letiges Konsultan Sosial, 2025)
This study aims to describe the collaborative learning strategy based on Islamic values implemented by Islamic Education (PAI) teachers at Muhammadiyah 1 Senior High School Surakarta, to enhance pedagogical competence and strengthen students' character. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, document analysis, and semi-structured interviews with seven key informants: the school headmaster, the vice headmaster for curriculum, and five subject teachers involved in interdisciplinary collaboration. Observations were conducted over one month during the learning process's planning, implementation, and reflection phases. The findings reveal that the formation of cross-subject teacher teams, microlearning, and routine reflective forums are the core strategies successfully implemented. These strategies strengthened the integration of Islamic values across all subjects and enhanced teachers' creativity and digital literacy. The active involvement of the headmaster as a transformational leader further supported a culture of innovation and collaboration within the school environment. The theoretical contribution of this study lies in its integrative, collaborative model grounded in Islamic values, which other schools with similar contexts can adapt. These findings highlight the importance of supportive leadership, flexible curricula, and technology as a medium for value-based education. This research encourages the development of value-based learning strategies within collaborative teaching practices as part of a broader character-based educational transformation.